An emulation–based execution control system evaluation tool: application to a furniture manufacturing group. (9th January 2012) - Klein, Thomas; André,
Changing the execution control system could have a significant impact on a manufacturing company performance. Indeed, the strongly competitive context does not enable any error, which reinforces the need for a detailed a priori improvement analysis. Our proposition relies on a discrete–event simulation architecture useful to evaluate different manufacturing control systems. This enables the control system to be run connected with a representative virtual shop floor to evaluate its performances. This tool enables several control systems to be validated and compared, with greater or lesser distribution of decision power. An industrial case study is presented, based on a French furniture manufacturer, to validate the implementation of a distributed control system.